Authenticity in Music - Rita Mardhatillah binti Umar Rauf; Nurulhamimi Abdul Rahman; Faezah Hamdan; Adee Arifin (Randwick International of Social Science Journal, 2023)
Authenticity in music is a complex that has intrigued musicians, scholars, and audiences for centuries. It refers to the perceived genuineness, sincerity, and originality of the musical expression, reflecting the artist's ability to convey genuine emotions and experiences. While authenticity is a subjective and evolving notion, it plays an essential role in shaping the listener's connection with the music and the artist. In the contemporary music, the pursuit of authenticity has been both celebrated and challenged. On one hand, artists who can genuinely express their thoughts and emotions through their craft often resonate deeply with audiences, fostering a sense of connection and understanding. This authenticity can be achieved through various means, such as personal storytelling, vulnerability, or innovative approaches to musical composition